The Effectiveness of Mandala Coloring Therapy on Stress Levels in the Elderly - Vinda Nuri Fadhila; Kartinah Kartinah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Psychological disorders in the elderly include dementia, anxiety, sleep disorders and depression. Anxiety is the most common disorder. Based on data from the Ministry of Health, emotional disorders in the elderly in Indonesia occur 10% in the age range of 65-74 years and 13% occur in the elderly aged more than 75 years. Elderly people who experience anxiety need good handling in reducing their anxiety otherwise it can cause cognitive damage and depression. Objective: aims to determine the effect of coloring therapy on anxiety and stress levels in the elderly conducted at Tresna Werdha Social Services, Pakem, Sleman, Yogyakarta. Method: This is a case report with a pre post test design on 10 elderly people. Patients were intervened in the form of mandala coloring therapy, then re-measured to assess anxiety and stress in the elderly. The samples in this study were 10 elderly women who experienced anxiety and stress. Patients were given an intervention in the form of coloring mandalas for ± 15 minutes. Results: The results obtained by doing coloring therapy can help reduce anxiety and stress levels in the elderly. Conclusions: coloring can help reduce anxiety and stress levels in the elderly.